Q: Evaluate$\newcommand{\dx}{\mathrm dx}\newcommand{\du}{\mathrm du}\newcommand{\dv}{\mathrm dv}\newcommand{\dtheta}{\mathrm d\theta}\newcommand{\dw}{\mathrm dw}$$$I=\int\limits_0^{\pi/2}\dx\,\frac {\left(\log\sin x\log\cos x\right)^2}{\sin x\cos x}$$

I'm out of ideas on what to do. I tried using the astute limit identity for integration, but that lead to nowhere, because it's simply the same integral i.e adding the two together, doesn't yield a simplification whatsoever$$I=\int\limits_0^{\pi/2}\dx\,\frac {\log^2\sin x\log^2\cos x}{\sin x\cos x}=\int\limits_0^{\pi/2}\du\,\frac {\log^2\cos u\log^2\sin u}{\cos u\sin u}$$I've looked into making a u-substitution, but have no idea where to begin. I plan to use a trigonometric identity, namely$$\sec x\csc x=\cot x+\tan x$$but I'm not sure what to do afterwards because we get$$I=\int\limits_0^{\pi/2}\dx\,\cot x\log^2\sin x\log^2\cos x+\int\limits_0^{\pi/2}\dx\,\tan x\log^2\sin x\log^2\cos x$$I would appreciate it if you guys gave me an idea on where to begin!

Also, as a side note, I've used \newcommand on \dx,\du,\dv, and \dw to automatically change to $\dx$, $\du$, $\dv$, and $\dw$ respectively, if you guys don't mind! Just to make it easier for the differential operator!

  • $\begingroup$ It seems to be $\frac{1}{24}(12\zeta(5) - \pi^2\zeta(3)) \approx 0.02413778999736$ $\endgroup$ – achille hui Jan 17 '18 at 5:13
  • 1
    $\begingroup$ Hint: change variable to $t = \sin(x)^2$ and get rid of all trigonometric function. $\endgroup$ – achille hui Jan 17 '18 at 5:48
  • $\begingroup$ What makes you say that it is simple ??? $\endgroup$ – Yves Daoust Jan 17 '18 at 9:04
  • $\begingroup$ What is this... A strange integral, and no Jack? Should we worry? $\endgroup$ – mathreadler Jan 17 '18 at 15:11

Change variable to $t = \sin^2 x$ and notice $$\begin{align}\frac{dx}{\sin x\cos x} &= \frac{\sin x\cos x dx}{\sin^2 x\cos^2 x} = \frac12\frac{dt}{t(1-t)}\\ \log\sin x \log\cos x &= \frac14\log\sin^2 x \log \cos^2 x = \frac14 \log t\log(1-t) \end{align} $$ The integral at hand can be rewritten as $$\mathcal{I} \stackrel{def}{=} \int_0^{\pi/2} \frac{(\log\sin x\log\cos x)^2}{\sin x\cos x} dx = \frac{1}{32}\int_0^1 \frac{\log^2 t \log^2(1-t)}{t(1-t)} dt$$ Since $\displaystyle\frac{1}{t(1-t)} = \frac1t + \frac{1}{1-t}$, by replacing $t$ by $1-t$ in part of the integral, we find

$$\begin{align} \mathcal{I} &= \frac{1}{16}\int_0^1 \frac{\log^2 t\log^2(1-t)}{t} dt = \frac{1}{48}\int_0^1 \log^2(1-t) d\log^3 t\\ &\stackrel{\text{I.by.P}}{=} \frac{1}{48}\left\{ \left[\log^2(1-t)\log^3 t\right]_0^1 + 2 \int_0^1 \log^3 t\frac{\log(1-t)}{1-t}dt\right\}\\ &= -\frac{1}{24}\int_0^1 \frac{\log^3 t}{1-t}\sum_{n=1}^\infty\frac{t^n}{n} dt = -\frac{1}{24}\int_0^1 \log^3 t\sum_{n=1}^\infty H_nt^n dt\\ &\stackrel{t = e^{-y}}{=} \frac{1}{24} \int_0^\infty y^3 \sum_{n=1}^\infty H_n e^{-(n+1)y} dy = \frac14 \sum_{n=1}^\infty \frac{H_n}{(n+1)^4} \end{align} $$ where $H_n$ are the $n^{th}$ harmonic number. By rearranging its terms, the last sum should be expressible in terms of zeta functions. I'm lazy, I just ask WA to evaluate the sum. As expected, last sum equals to $2\zeta(5) - \frac{\pi^2}{6}\zeta(3)$${}^\color{blue}{[1]}$.

As a consequence, the integral at hand equals to:

$$\mathcal{I} = \frac{12\zeta(5) - \pi^2\zeta(3)}{24} \approx 0.024137789997360933616411382857235691008...$$


  • $\color{blue}{[1]}$ It turns out we can compute this sum using an identity by Euler. $$2\sum_{n=1}^\infty \frac{H_n}{n^m} = (m+2)\zeta(m+1) - \sum_{n=1}^{m-2}\zeta(m-n)\zeta(n+1),\quad\text{ for } m = 2, 3, \ldots$$ In particular, for $m = 4$, this identity becomes $$\sum_{n=1}^\infty \frac{\zeta(n)}{n^4} = 3\zeta(5) - \zeta(2)\zeta(3)$$ and we can evaluate our sum as $$\begin{align}\mathcal{I} &= \frac14\sum_{n=1}^{\infty}\frac{H_{n}}{(n+1)^4} = \frac14\sum_{n=1}^{\infty}\left(\frac{H_{n+1}}{(n+1)^4}-\frac{1}{(n+1)^5}\right) = \frac14\left(\sum_{n=1}^\infty \frac{H_n}{n^4} - \zeta(5)\right)\\ &= \frac14(2\zeta(5) - \zeta(2)\zeta(3)) = \frac{12\zeta(5) - \pi^2\zeta(3)}{24} \end{align} $$
  • $\begingroup$ How did you get to the step below?$$\mathcal{I} = \frac{1}{16}\int_0^1 \frac{\log^2 t\log^2(1-t)}{t} dt = \frac{1}{48}\int_0^1 \log^2(1-t) d\log^3 t$$ $\endgroup$ – Crescendo Jan 17 '18 at 20:03
  • $\begingroup$ @Crescendo $$\begin{align}&\int_0^1\frac{\log^2(t)\log^2(1-t)}{t(1-t)}dt = \int_0^1\log^2(t)\log^2(1-t)\left(\frac{1}{t} + \frac{1}{1-t}\right)dt\\ \stackrel{s=1-t}{=} & \int_0^1\frac{\log^2(t)\log^2(1-t)}{t}dt + \int_0^1\frac{\log^2(1-s)\log^2(s)}{s}ds = 2\int_0^1\frac{\log^2(t)\log^2(1-t)}{t}dt \end{align} $$ and $$d\log^3(t) = \frac{d(\log^3(t))}{dt} dt = 3\log^2(t)\frac{d\log(t)}{dt} dt = 3 \frac{\log^2(t)}{t}dt$$ $\endgroup$ – achille hui Jan 17 '18 at 23:23
  • $\begingroup$ So you're using differentiation under the integral? I'm having trouble understanding your notation $d\,\log^3t$ for some reason... $\endgroup$ – Crescendo Jan 17 '18 at 23:53
  • $\begingroup$ @Crescendo For your purpose, you can either view $\int f(x)dg(x)$ as a short-hand for $\int f(x)g'(x)dx$ or as a Riemann–Stieltjes integral. I personally view those things as integration involving differential forms. (which have richer algebraic properties and allow more flexiable manipulation of the expression) $\endgroup$ – achille hui Jan 18 '18 at 0:54
  • $\begingroup$ One last question: How does$$\frac {1}{1-t}\sum\limits_{n\geq1}\frac {t^n}n=\sum\limits_{n\geq1}H_n t^n$$I think you represented the $1/(1-t)$ fraction as its infinite geometric sequence, but I'm not seeing how that equals the right-hand side. $\endgroup$ – Crescendo Feb 10 '18 at 2:03

I will work with the integral found after a substitution of $t = \sin^2 x$ has been made so that $$I = \int_0^{\pi/2} \frac{\ln^2 (\sin x) \ln^2 (\cos x)}{\sin x \cos x} \, dx = \frac{1}{32} \int_0^1 \frac{\ln^2 t \ln^2 (1 - t)}{t (1 - t)} \, dt.$$

The first method that comes to mind is to evaluate the integral appearing to the right as the derivative of a beta function. Since $$\text{B} (x,y) = \int_0^1 t^{x - 1} (1 - t)^{y - 1} \, dt,$$ we see that $$\lim_{x \to 0^+} \lim_{y \to 0^+} \partial^2_x \partial^2_y \text{B}(x,y) = \int_0^1 \frac{\ln^2 t \ln^2 (1 - t)}{t (1 - t)} \, dt.$$ Thus $$I = \frac{1}{32} \lim_{x \to 0^+} \lim_{y \to 0^+} \partial^2_x \partial^2_y \text{B}(x,y).$$ While the above calculation is doable, it is far from trivial (at least "by hand") and will accordingly not be given here.

As a second method, I will make use of the following Maclaurin series expansion for the term $\ln^2 (1 - t)$ which is given by $$\ln^2 (1 - t) = 2 \sum_{n = 2}^\infty \frac{H_{n - 1}}{n} t^n, \qquad |t| < 1, \tag1$$ where $H_n$ is the $n$th Harmonic number. A proof of this result can be found here.

As $$\frac{1}{t(1 - t)} = \frac{1}{t} + \frac{1}{1 - t},$$ we can write the integral $I$ as $$I = \frac{1}{32} \int_0^1 \frac{\ln^2 t \ln^2 (1 - t)}{t} \, dt + \frac{1}{32} \frac{\ln^2 t \ln^2 (1 - t)}{1 - t} \, dt.$$ If in the second of these integrals we enforce a substitution of $t \mapsto 1 - t$ we have $$I = \frac{1}{16} \int_0^1 \frac{\ln^2 t \ln^2 (1 - t)}{t} \, dt.$$

Replacing the term $\ln^2(1 - t)$ with its Maclaurin series expansion, after interchanging the summation with the integral sign we have $$I = \frac{1}{8} \sum_{n = 2}^\infty \frac{H_{n - 1}}{n} \int_0^1 t^{n - 1} \ln^2 t \, dt.$$ The integral that results can be readily found using integration by parts twice. The result is $$\int_0^1 t^{n - 1} \ln^2 t \, dt = \frac{2}{n^3}.$$ Thus $$I = \frac{1}{4} \sum_{n = 2}^\infty \frac{H_{n - 1}}{n^4}.$$

Since $$H_n = H_{n - 1} + \frac{1}{n},$$ we have $$I = \frac{1}{4} \left [\sum_{n = 2}^\infty \frac{H_n}{n^4} - \sum_{n = 2}^\infty \frac{1}{n^5} \right ] = \frac{1}{4} \left [\sum_{n = 1}^\infty \frac{H_n}{n^4} - \sum_{n = 1}^\infty \frac{1}{n^5} \right ].$$

The value for the Euler sum is well-known (see here for example). It is $$\sum_{n = 1}^\infty \frac{H_n}{n^4} = 3 \zeta (5) - \zeta (2) \zeta (3),$$ while the second sum is just the zeta function $\zeta (5)$. Thus $$I = \frac{1}{4} \big{[}3 \zeta (5) - \zeta (2) \zeta (3) - \zeta (5) \big{]},$$ or $$\int_0^{\pi/2} \frac{\ln^2 (\sin x) \ln^2 (\cos x)}{\sin x \cos x} \, dx = \frac{1}{4} \big{[} 2 \zeta (5) - \zeta (2) \zeta (3) \Big{]}.$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.